Tratamiento Clínico Más Eficaz Para Tumor Venéreo Transmisible Administrado Vía Subcutánea O Vía Intravenosa, Teniendo En Cuenta El Bienestar Animal (Machos Y Hembras). Monografía (2023)
This paper covers the relevant aspects of the canine transmissible venereal tumor CTVT, the type of tumor, the signs found in the canine, the anatomical places where it occurs most frequently and the treatment with vincristine sulfate subcutaneous route and intravenously and in which we have more welfare in the canine. Likewise, different epidemiological studies and case reports of the disease treated with vincristine by the different routes of administration were analyzed.